Unilateral trade liberalization in the Melitz model: A note - Gabriel Felbermayr; Benjamin Jung (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
In the two-country Melitz (2003) model, unilateral trade liberalization is often cast as a reduction of iceberg transportation costs and wages are determined by a linear outside sector. We show that welfare results reverse when wages adjust and trade frictions are revenue-generating tariffs.
urn:nbn:de:bsz:21-opus-60796
Keywords: F12; R12; 330; monopolistic competition; heterogeneous firms; international trade; trade policy; Allokation; Außenwirtschaft; Markteintritt; Branchenentwicklung; Produktivität; Außenhandelsliberalisierung; Lohn; Wohlfahrtseffekt; Theorie